(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2024)
The right to private property is enshrined as a fundamental and constitutional right, recognized and protected by Article 30 of the Constitution and Article 1 of the Additional Protocol to the European Convention on Human Rights. Both domestic and international legal frameworks ensure the inviolability of private property, safeguarding it from unjustified interventions by state bodies and third parties. However, instances of private ownership restriction, such as expropriation, may occur, wherein private property is transferred to state or municipal ownership in pursuit of public interest, subject to fair compensation, which must not fall below the market value, while respecting the right of appeal of the affected individual, the former owner, regarding the compensation amount. This paper aims to examine the legality of the expropriation process and the protection of the interests of former owners within this procedure. According to the European Convention on Human Rights, state imposed restrictions on property rights are legitimate if they fulfill three main criteria: legality, ensuring compliance with established legal standards; necessity, serving a public or general interest; and proportionality, commensurate with the sought objective. Domestic legislation should ensure appropriate procedural measures to shield expropriated former owners from arbitrary actions. The methods of ensuring effective protection for the rights of individuals impacted by expropriation will be explored. Additionally, this paper will delve into the methodology for determining compensation amounts in expropriation cases, the expropriation process itself, and procedural safeguards against baseless and capricious decisions by state authorities.